A single crystal morphology lithium ion battery ternary positive electrode material and its preparation method and application
By preparing the ternary cathode material of lithium-ion battery with single crystal morphology, the problem of prone to rupture in traditional materials during processing and circulation is solved, high electrochemical performance and stability is achieved, and it is suitable for new energy vehicle batteries.
Patent Information
- Application Number
- CN202210645933.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-08
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-06-08
AI Technical Summary
The spherical secondary particles of traditional commercial NCM positive electrode materials are prone to rupture during the rolling process and circulation of the electrode sheet, resulting in a decrease in electrochemical properties.
A lithium-ion battery ternary positive electrode material using a single crystal morphology is LiNixCoyMn1-x-yAaO2. A single crystal material with a median particle size D50 of 1 to 10 μm is prepared by preparing a metal salt solution, a precipitant and an additive solution, and reacting and sintering.
It achieves high tap density, excellent processability, slow capacity attenuation and excellent electrochemical properties at high temperatures or high voltages, avoiding the rupture of the material during circulation, and improving stability and circulation performance.
Smart Images

Figure CN114843504B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion battery electrode materials, and particularly relates to a ternary cathode material for lithium-ion batteries with a single crystal morphology, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have dominated the field of mobile electronic devices. Among all the components of lithium-ion batteries, the cathode material plays a very important role, which determines the electrochemical performance and cost of the battery. The layered lithium nickel cobalt manganate LiNi 1-x-y Co x Mn y O2 (NCM) ternary cathode material has become one of the mainstream cathode materials for power batteries because of its advantages such as high specific capacity, high discharge voltage, high energy density, and good rate performance, and can provide a longer cruising range and a faster charging speed for new energy vehicles.
[0003] At present, the morphology of traditional commercial NCM cathode materials is spherical secondary particles with a diameter of about 10 μm, and the secondary particles are composed of nano- or sub-micron primary particles tightly agglomerated together. However, such spherical secondary particles with this morphology are prone to cracking during the pole piece rolling process or during repeated cycling, resulting in a decrease in electrochemical performance. Summary of the Invention
[0004] The present invention provides a ternary cathode material for lithium-ion batteries with a single crystal morphology, a preparation method thereof, and an application thereof, which has a high tap density, excellent processability, slow capacity decay, and excellent electrochemical performance at high temperature or high voltage.
[0005] The ternary cathode material for lithium-ion batteries with a single crystal morphology provided by the present invention has a chemical general formula of LiNi x Co y Mn 1-x-y A a O2, where 0.5 ≤ x < 1, 0 < y ≤ 0.5, 0 < x + y ≤ 0.5, 0 < a ≤ 0.01; A is at least one of additive modification elements Mg, Ca, and Sr; the median particle size D50 of the ternary cathode material for lithium-ion batteries with a single crystal morphology is 1 - 10 μm.
[0006] Preferably, the median particle size D50 of the ternary cathode material for lithium-ion batteries with a single crystal morphology is 3 - 5 μm.
[0007] The preparation method of the ternary cathode material for lithium-ion batteries with a single crystal morphology provided by the present invention includes the following steps:
[0008] 1) Prepare a metal salt solution: weigh nickel salt, cobalt salt and manganese salt in a molar ratio of x:y:(1-xy), dissolve them in deionized water, mix them evenly, and obtain a metal salt solution; prepare a precipitant, an additive solution and a base solution;
[0009] 2) Pump the metal salt solution, precipitant and additive solution of step 1) into the bottom liquid of step 1) to react at a suitable temperature, pH and stirring speed. After the reaction is completed, age, wash and dry to obtain a carbonate precursor Ni x Co y Mn 1-x-y A a CO3;
[0010] 3) The carbonate precursor Ni prepared in step 2) x Co y Mn 1-x-y A a CO3 and lithium source are mixed evenly, sintered in an oxygen atmosphere furnace, ground, crushed and sieved after cooling to obtain single crystal morphology of lithium-ion battery ternary positive electrode material LiNi x Co y Mn 1-x-y A a O2.
[0011] Preferably, in step 1), the nickel salt is at least one of nickel sulfate, nickel nitrate and nickel chloride; the cobalt salt is at least one of cobalt sulfate, cobalt nitrate and cobalt chloride; the manganese salt is at least one of manganese sulfate, manganese nitrate and manganese chloride; and the total concentration of metal cations in the metal salt solution is 0.5 to 2.0 mol / L.
[0012] Preferably, in the step 1), the precipitant is one of Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 1 to 3 mol / L or a mixture thereof, wherein the mixture is composed of Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 1 to 3 mol / L in a volume ratio of 1 to 200:1 to 200:1 to 200; the additive is a chloride salt of the modifying element A, the chloride salt of the modifying element A is at least one of MgCl2, CaCl2 and SrCl2, and the concentration of the additive is 0.01 to 1 mol / L; the base solution is prepared by deionized water and NH4HCO3 and NH3·H2O solutions with a concentration of 1 to 3 mol / L in a volume ratio of 1 to 200:1 to 200:1 to 200.
[0013] Preferably, in the step 2), the pumping speeds of the metal salt solution, the precipitant and the additive solution are 1 to 100 mL / min respectively, the pumping time is the same as the reaction time, and the pumping is continued during the reaction time; the reaction temperature is 30 to 60°C, the pH value is 7 to 9, the stirring speed is 300 to 900 r / min, the reaction time is 8 to 48 h, the aging time is 6 to 16 h, and the solution is washed with deionized water at 50 to 90°C, the drying temperature is maintained at 60 to 150°C, and the drying time is 6 to 20 h.
[0014] Preferably, in step 2), Ni x Co y Mn 1-x-y A a The content a of the additive element A in CO3 is 0.001 to 0.01.
[0015] Preferably, in step 3), the lithium source is at least one of lithium carbonate, lithium hydroxide and lithium nitrate; the carbonate precursor Ni x Co y Mn 1-x-y A a The molar ratio of CO3 to Li / (Ni+Co+Mn) in the lithium source is 1.00-1.10; the carbonate precursor Ni x Co y Mn 1-x-y A a CO3 and lithium source are mixed in a high-speed mixer at a speed of 400 to 800 r / min for 30 to 60 minutes.
[0016] Preferably, in step 3), the sintering process is: heating rate is 1-10°C / min, the first stage sintering temperature is 500-700°C, and the sintering time is 4-10h; then the temperature is raised to the second stage sintering temperature of 800-1000°C, and the sintering time is 8-14h.
[0017] The invention provides a lithium ion battery ternary positive electrode material with a single crystal morphology and is used in lithium ion batteries.
[0018] Beneficial effects of the present invention:
[0019] (1) The present invention has the characteristics of simple preparation process, easy control of preparation process, compatibility with existing preparation equipment of ternary positive electrode materials, and easy industrial promotion.
[0020] (2) LiNi prepared by the present invention x Co y Mn 1-x-y A aThe O2 positive electrode material has a single crystal morphology, a uniform single crystal particle size distribution, a primary particle size of micrometer level, a median particle size D50 between 1 and 10 μm, and the particle size is easy to control.
[0021] (3) The single crystal LiNi prepared by the present invention x Co y Mn 1-x-y A a The O2 positive electrode material has a standard layered structure, which can effectively avoid the phenomenon of particle rupture during the cycle, alleviate the side reaction with the electrolyte, improve the stability, and improve its cycle performance at a high cut-off voltage of 4.5V. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The finished single crystal LiNi in Example 1 0.5 Co 0.2 Mn 0.3 Sr 0.005 Scanning electron microscope image of O2 cathode material, magnified 2000 times;
[0023] Figure 2 The finished single crystal LiNi in Example 2 0.6 Co 0.2 Mn 0.2 Ca 0.006 Scanning electron microscope image of O2 cathode material, magnified 2000 times;
[0024] Figure 3 The finished single crystal LiNi in Example 3 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 Scanning electron microscope image of O2 cathode material, magnified 2000 times;
[0025] Figure 4 The finished single crystal LiNi in Comparative Example 1 0.83 Co 0.11 Mn 0.06 Scanning electron microscope image of O2 cathode material, magnified 2000 times;
[0026] Figure 5 The finished single crystal LiNi in Example 1 0.5 Co 0.2 Mn 0.3 Sr 0.005 4.5V cycle curve of O2 cathode material;
[0027] Figure 6 The finished single crystal LiNi in Example 2 0.6 Co0.2 Mn 0.2 Ca 0.006 4.5V cycle curve of O2 cathode material;
[0028] Figure 7 The finished single crystal LiNi in Example 3 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 4.5V cycle curve of O2 cathode material;
[0029] Figure 8 The finished single crystal LiNi in Comparative Example 1 0.83 Co 0.11 Mn 0.06 4.5V cycle curve of O2 positive electrode material. DETAILED DESCRIPTION
[0030] In order to further illustrate the technical means adopted by the present invention to achieve the intended purpose, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the following embodiments are only further explanations of the present invention, rather than being used to limit the present invention, and the embodiments of the present invention are not limited to the following embodiments.
[0031] The materials involved in the following examples and comparative examples can all be obtained from commercial channels.
[0032] Unless otherwise specified, the percentages in the following examples and comparative examples are all molar percentages.
[0033] Example 1
[0034] (1) nickel sulfate, cobalt sulfate and manganese sulfate were weighed according to the ratio of n(Ni):n(Co):n(Mn)=5:2:3 to prepare a metal salt solution so that the total concentration of metal cations was 1 mol / L; Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 1.5 mol / L were mixed in a volume ratio of 120:1:1 to prepare a precipitant; a SrCl2 solution with a concentration of 0.1 mol / L was prepared as an additive solution; NH4HCO3 and NH3·H2O solutions with a concentration of 1.5 mol / L were prepared, and then mixed with deionized water in a volume ratio of 120:1:1 to prepare a base solution.
[0035] (2) Add 5L of the above-mentioned base liquid to the reactor, then pump the above-mentioned metal salt solution at a rate of 15mL / min, the precipitant at a rate of 10mL / min, and the additive solution at a rate of 1mL / min into the reactor simultaneously. The pumping time is the same as the reaction time. The pumping is continued during the reaction time. The reaction temperature is maintained at 50°C, the pH value is 7.6, the stirring speed is 800r / min, and the reaction is carried out for 30h and then aged for 14h. The product is washed with deionized water at 70°C and dried at 90°C for 12h to obtain a carbonate precursor Ni 0.5 Co 0.2 Mn 0.3 Sr 0.005 CO3.
[0036] (3) The prepared carbonate precursor Ni 0.5 Co 0.2 Mn 0.3 Sr 0.005 CO3 and lithium carbonate were mixed in a high-speed mixer at a molar ratio of Li / (Ni+Co+Mn)=1.05 at a speed of 600r / min for 60min. After mixing, the mixture was placed in a tubular atmosphere furnace, introduced into an oxygen atmosphere, heated to 650°C at a heating rate of 5°C / min, kept warm for 4h, then heated to 970°C at a heating rate of 5°C / min, kept warm for 12h, and cooled to room temperature with the furnace. The product was ground, crushed, and sieved to obtain a high-voltage single crystal LiNi with a median particle size D50 of 5.6μm. 0.5 Co 0.2 Mn 0.3 Sr 0.005 O2 positive electrode material.
[0037] Example 2
[0038] (1) nickel sulfate, cobalt sulfate and manganese sulfate were weighed according to the ratio of n(Ni):n(Co):n(Mn)=6:2:2 to prepare a metal salt solution so that the total concentration of metal cations was 1 mol / L; Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 2.0 mol / L were mixed in a volume ratio of 100:1:1 to prepare a precipitant; a CaCl2 solution with a concentration of 0.15 mol / L was prepared as an additive solution; NH4HCO3 and NH3·H2O solutions with a concentration of 2.0 mol / L were mixed with deionized water in a volume ratio of 120:1:1 to prepare a base solution.
[0039] (2) Add 5L of the above-mentioned base liquid to the reactor, pump the above-mentioned metal salt solution at a rate of 20mL / min, the precipitant at a rate of 10mL / min, and the additive solution at a rate of 1.5mL / min into the reactor simultaneously, the pumping time is the same as the reaction time, and the pumping is continued during the reaction time, the reaction temperature is maintained at 45°C, the pH value is 7.8, the stirring speed is 750r / min, the reaction is carried out for 36h, and then the reaction is aged for 12h, washed with deionized water at 80°C, and dried at 120°C for 10h to obtain a carbonate precursor Ni 0.6 Co 0.2 Mn 0.2 Ca 0.01 CO3.
[0040] (3) The prepared carbonate precursor Ni 0.6 Co 0.2 Mn 0.2 Ca 0.006 CO3 and lithium hydroxide were mixed in a high-speed mixer at a speed of 500r / min for 50min according to a molar ratio of Li / (Ni+Co+Mn)=1.06. After mixing, the mixture was placed in a tubular atmosphere furnace, introduced into an oxygen atmosphere, heated to 680℃ at a heating rate of 3℃ / min, kept warm for 10h, then heated to 940℃ at a heating rate of 3℃ / min, kept warm for 10h, and cooled to room temperature with the furnace. The product was ground, crushed, and sieved to obtain a high-voltage single crystal LiNi with a median particle size D50 of 3.7μm. 0.6 Co 0.2 Mn 0.2 Ca 0.006 O2 positive electrode material.
[0041] Example 3
[0042] (1) nickel sulfate, cobalt sulfate and manganese sulfate were weighed according to the ratio of n(Ni):n(Co):n(Mn)=83:12:5 to prepare a metal salt solution so that the total concentration of metal cations was 1.5 mol / L; Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 2.5 mol / L were mixed in a volume ratio of 125:1:1 to prepare a precipitant; MgCl2 and SrCl2 solutions with a concentration of 0.1 mol / L were prepared as additive solutions; NH4HCO3 and NH3·H2O solutions with a concentration of 2.5 mol / L were mixed with deionized water in a volume ratio of 125:1:1 to prepare a base solution.
[0043] (2) Add 5L of the above-mentioned base liquid to the reactor, then pump the above-mentioned metal salt solution at a rate of 20mL / min, the precipitant at a rate of 12mL / min, and the additive solution at a rate of 1.5mL / min into the reactor simultaneously. The pumping time is the same as the reaction time. The pumping is continued during the reaction time. The reaction temperature is maintained at 55°C, the pH is 7.5, and the stirring speed is 750r / min. After reacting for 32h, it is aged for 12h, washed with deionized water at 80°C, and dried at 80°C for 12h to obtain a carbonate precursor Ni 0.83 Co 0.1 2Mn 0.05 Mg 0.003 Sr 0.003 CO3.
[0044] (3) The prepared carbonate precursor and lithium hydroxide were mixed in a high-speed mixer at a molar ratio of Li / (Ni+Co+Mn)=1.04 at a speed of 600r / min for 45min. After mixing, the mixture was placed in a tubular atmosphere furnace, an oxygen atmosphere was introduced, and the mixture was heated to 700°C at a heating rate of 6°C / min, kept warm for 6h, and then heated to 850°C at a heating rate of 6°C / min, kept warm for 12h, and cooled to room temperature with the furnace. The product was ground, crushed, and sieved to obtain a high-voltage single crystal LiNi with a median particle size D50 of 4.3μm. 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 O2 positive electrode material.
[0045] Comparative Example 1
[0046] (1) nickel sulfate, cobalt sulfate and manganese sulfate were weighed according to the ratio of n(Ni):n(Co):n(Mn)=83:11:6 to prepare a metal salt solution so that the total concentration of metal cations was 1.0 mol / L; Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 1.5 mol / L were mixed in a volume ratio of 75:1:1 to prepare a precipitant; NH4HCO3 and NH3·H2O solutions with a concentration of 1.5 mol / L were mixed with deionized water in a volume ratio of 75:1:1 to prepare a base solution.
[0047] (2) Add 5L of the above-mentioned base liquid to the reactor, and then pump the above-mentioned metal salt solution into the reactor at a speed of 15mL / min and the precipitant at a speed of 10mL / min. The pumping time is the same as the reaction time. The pumping is continued during the reaction time, and the reaction temperature is maintained at 55°C, the pH is 7.6, and the stirring speed is 750r / min. After reacting for 28h, it is aged for 16h, washed with deionized water at 80°C, and dried at 80°C for 16h to obtain a carbonate precursor Ni0.83 Co 0.11 Mn 0.06 CO3.
[0048] (3) The prepared carbonate precursor and lithium hydroxide were mixed in a high-speed mixer at a molar ratio of Li / (Ni+Co+Mn)=1.05 at a speed of 600r / min for 30min. After mixing, the mixture was placed in a tubular atmosphere furnace, an oxygen atmosphere was introduced, and the mixture was heated to 500°C at a heating rate of 5°C / min, kept warm for 4h, and then heated to 800°C at a heating rate of 5°C / min, kept warm for 14h, and cooled to room temperature with the furnace. The product was ground, crushed, and sieved to obtain LiNi 0.83 Co 0.11 Mn 0.06 O2 positive electrode material.
[0049] The morphology of the positive electrode materials obtained in Examples 1 to 3 and Comparative Example 1 was analyzed using a scanning electron microscope to obtain scanning electron microscope images thereof, as shown in FIG. Figures 1 to 4 shown.
[0050] The positive electrode materials obtained in Examples 1 to 3 and Comparative Example 1 were assembled into button cells using a technical method for preparing positive electrode materials into lithium-ion button cells that is well known to those skilled in the art. The electrochemical performance tests were carried out on a blue-electric test system. The results are shown in Table 1.
[0051] Table 1 shows the electrochemical properties of button cells (2.8-4.5V, 25°C)
[0052]
[0053]
[0054] Table 1 lists the electrochemical performance data of the positive electrode materials prepared in Examples 1 to 3 and Comparative Example 1. It can be found that compared with Comparative Example 1, the positive electrode materials prepared in Examples 1 to 3 have advantages in discharge specific capacity, first coulombic efficiency and capacity retention rate.
[0055] from Figure 1 to Figure 3 It can be seen that the positive electrode material prepared by the method of the present invention has a dispersed micron-sized single crystal morphology, while the positive electrode material prepared in Comparative Example 1 is agglomerated secondary spherical particles; Examples 1 to 3 optimize the electrochemical properties of the material and have good electrochemical stability at a high cut-off voltage of 4.5V.
[0056] The above description is not intended to limit the present invention, and the present invention is not limited to the above embodiments. Any changes, modifications, additions or substitutions made by those skilled in the art within the essential scope of the invention shall also fall within the protection scope of the present invention.
Claims
1. A single crystal morphology lithium ion battery ternary cathode material, whose chemical formula is LiNi 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 O2; the median particle size D50 of the single crystal morphology of the lithium ion battery ternary positive electrode material is 1 to 10 μm; The method for preparing the single crystal morphology lithium ion battery ternary positive electrode material comprises the following steps: (1) nickel sulfate, cobalt sulfate and manganese sulfate were weighed according to the ratio of n(Ni):n(Co):n(Mn)=83:12:5 to prepare a metal salt solution so that the total concentration of metal cations was 1.5 mol / L; Na2CO3, NH4HCO3 and NH3·H2O solutions with a concentration of 2.5 mol / L were mixed in a volume ratio of 125:1:1 to prepare a precipitant; MgCl2 and SrCl2 solutions with a concentration of 0.1 mol / L were prepared as additive solutions; NH4HCO3 and NH3·H2O solutions with a concentration of 2.5 mol / L were mixed with deionized water in a volume ratio of 125:1:1 to prepare a base solution; (2) Add 5L of the above-mentioned base liquid to the reactor, then pump the above-mentioned metal salt solution at a rate of 20mL / min, the precipitant at a rate of 12mL / min, and the additive solution at a rate of 1.5mL / min into the reactor simultaneously. The pumping time is the same as the reaction time. The pumping is continued during the reaction time. The reaction temperature is maintained at 55°C, the pH is 7.5, and the stirring speed is 750r / min. After reacting for 32h, it is aged for 12h, washed with deionized water at 80°C, and dried at 80°C for 12h to obtain a carbonate precursor Ni 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 CO3; (3) The prepared carbonate precursor and lithium hydroxide were mixed in a high-speed mixer at a molar ratio of Li / (Ni+Co+Mn)=1.04 at a speed of 600 r / min for 45 min. After mixing, the mixture was placed in a tubular atmosphere furnace, an oxygen atmosphere was introduced, and the mixture was heated to 700°C at a heating rate of 6°C / min, kept warm for 6 h, and then heated to 850°C at a heating rate of 6°C / min, kept warm for 12 h, and cooled to room temperature with the furnace; the product was ground, crushed, and sieved to obtain a high-voltage single crystal LiNi with a median particle size D50 of 4.3 μm. 0.83 Co 0.12 Mn 0.05 Mg 0.003 Sr 0.003 O2 positive electrode material.
2. Application of the single crystal morphology lithium ion battery ternary positive electrode material made according to the material of claim 1 in lithium ion batteries.
Citation Information
Patent Citations
Preparation method of ternary precursor containing Mg and Al
CN106654197A
Ternary positive electrode material of high-nickel monocrystal-like lithium ion battery and preparation method thereof
CN110931768A
Single-crystal ternary positive electrode material, preparation method thereof and lithium ion battery
CN112018372A
Preparation method of anion in-situ doped high-nickel ternary positive electrode material
CN114162881A